Predictive testing for Huntington's disease: after the gene. The United Kingdom Huntington's Disease Prediction Consortium. Issue 12 (December 1993) - Simpson, S A; Harding, A E
Abstract : The discovery of a mutation responsible for Huntington's disease (HD) offers the possibility of accurate predictive testing, as well as hope for treatment or prevention of this disease. We urge caution in the use of this new test as considerable ethical and counselling problems still exist, and new issues have arisen. The current guidelines for predictive testing should still apply, since it remains vital that subjects and their families have time to come to terms with the diagnosis of HD, and the implications of testing. Mutation analysis may allow the diagnosis of HD in isolated cases, or reverse a test result produced using linkage. Problems will arise as those at 25% risk may now receive a result despite the lack of support of their parent at 50% risk who may not wish to have their own status defined. In addition, couples who seek the exclusion test in pregnancy may find it difficult to investigate the pregnancy without producing information on themselves. Different centres should cooperate in maintaining the confidentiality of family members, ensuring that adequate counselling is given before results are produced which may affect the wider family.